Маркетингове дослідження моделі поведінки споживача на ринку соняшнику - Куліш, Тетяна Володимирівна; Кулиш, Татьяна Владимировна; Kulish, Tetiana (My University, 2016)
UK: Необхідність маркетингового дослідження моделі поведінки споживача на ринку соняшнику викликана мінливими умовами ринкової кон’юнктури. Правильна сформована модель поведінки споживача на ринку сприятиме зростанню прибутку підприємств, підвищенню конкурентоспроможності продукції на внутрішньому та світовому ринках. Мета маркетингового дослідження: визначення споживчих мотивацій та рівня попиту на протягом маркетингового року. Для отримання інформації проведено польові дослідження за допомогою експертного анкетування. Результати дослідження дозволять вдало організувати збутову політику підприємства. План реалізації соняшнику має включати: розрахунок потреби в соняшниковому насінні; визначення максимально можливих обсягів зберігання соняшникового насіння на власному складі; обґрунтування доцільності зберігання соняшникового насіння на власному складі чи на складах суб’єктів господарювання, що надають послуги зі зберігання соняшникового насіння; планування реалізаційної діяльності соняшнику для максимізації прибутків за рахунок зберігання та реалізації з вигідними цінами протягом маркетингового року. EN: Setting objectives.The need for marketing research models of consumer behavior in the market of sunflower caused by changing conditions in market conditions. Well-formed model of consumer behavior in the market, to increase the profits of enterprises, improve product competitiveness in domestic and global markets. Production of oilseeds occupies a leading position in the agricultural sector of the state. The marketing problem is the market research sunflower Zaporozhye region. The purpose of market research: the study of consumer motivations and level of demand for the marketing year. Objectives of the study: to evaluate the level of demand for sunflower seeds during the marketing year; explore consumer motivation in carrying out purchases of sunflower seeds during the marketing year; identify the most successful marketing combination for the implementation of sunflower seeds for the marketing year. For information conducted field research with the help of expert survey. Research results. In Ukraine, the sunflower is the main raw material for the production of oil and ensuring public oil fatty kinds of products. In the domestic market there is a significant demand for sunflower seeds by large processing companies. The main activities of respondents are purchasing grain and oil crops for their own purposes (processing) or for resale. In enterprises on processing sunflower seeds formed part of a permanent contingent of suppliers of seeds, but not enough to cover the demand for raw materials during the year. So they have to carry out procurement of raw materials from neighboring regions and suppliers interested in expanding the range (86%). When looking for suppliers of enterprise prefer to work for good relations, but expanding the range of suppliers at 50% of respondents are turning to advertising media (Internet, newspapers, TV). Conclusions. Results of the study will successfully organize the sales policy of the company. Sunflower implementation plan should include: calculation needs sunflower seeds; determine the maximum amounts of storage sunflower seeds on its part; rationale storage sunflower seeds on its part or in warehouses entities that provide services for the storage of sunflower seeds; Sunflower realizable planning activities to maximize profits at the expense of storage and sale of the best prices for the marketing year.
Market research behaviors consumer market of sunflower
Keywords: маркетингові дослідження; ринок насіння соняшнику; опитування; респонденти; експерти; анкета; marketing research; market sunflower seeds; survey respondents experts; questionnaire